Gutta percha verses resilon: An in vitro comparison of fracture resistance in endodontically treated teeth - Jyothi Shashidhar; C Shashidhar (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of this study was to evaluate and compare the fracture resistance of endodontically treated teeth filled with gutta percha and Resilon using lateral and vertical condensation methods. Materials and Methods: A total of 75 freshly extracted single-rooted teeth were selected. All samples were instrumented with profile 4% Ni-Ti rotary instruments. Samples were randomly divided into five groups of 15 samples each: Group 1 was obturated using lateral condensation with gutta percha and AH -26 sealer. Group 2 was obturated using vertical condensation with gutta-percha and AH-26. Group 3 was obturated with Resilon and epiphany using lateral condensation technique. Group 4 was obturated with Resilon and epiphany using vertical condensation method. Group 5 received no filling. Restored teeth were subjected to compressive loading in a universal testing machine. Results: One-way ANOVA test showed significant difference among the groups (P < 0.05). The mean and SD values for the groups are as follows: Group 1 - (773.3 ± 148.1), Group 2 - (769.9 ± 170.5), Group 3 - (928.1 ± 135.4), Group 4 - (902.6 ± 120.8), and Group 5 - (766.0 ± 152.0). It was seen that samples of Group 3 showed the highest fracture resistance followed by Group 4, Group 1, and Group 2. Group 5 showed the least fracture resistance. Conclusion: Resilon-epiphany obturated roots using lateral condensation method showed higher fracture resistance compared with gutta percha-AH 26 groups on vertical loading.